Kejadian dan Terapi Babesiosis dengan Clindamycin pada Kucing (THE INCIDENCE AND TREATMENT OF BABESIOSIS WITH CLINDAMYCIN IN CAT) - Wulansari, Retno; Soesatyoratih, Raden Roro; ., Suryono (Jurnal Veteriner, 2014)
The patients : 5 cats, came to “Klinik Hewan Cimanggu”, complains from the clients were includinglistlessness, anorexia, diarrhea, and constipation. From the Physical examination they showed a palemucous membrane, hyperaemic on sclera, larger of cranial abdominal . Laboratory finding on bloodssmear showed blood parasites in red cells that suspected as Babesia sp. One of them concurrently withhaemobartonella sp infections. The general result of blood laboratory test showed anemia andthrombocytopenia. Its treated by clindamycin (10 mg/Kg BW) and multivitamin twice a day for 3 weeksand parasitemia level in 1000 red cell was count before treated. Reexamination of smear red cell wasdone during and after treatment. In general they had demonstrated the decrease of parasitemia level.Some of them didn’t showed any changes of parasitemia level, however they showed morphological changesthat indicate inactive condition of parasites. The decrease of parasitemia level or the morphologicalchanges of parasites indicates that the development of parasitemia level has been depressed, so theclinical signs decreased and the animal’s condition improved. It believed that clindamycin inhibits proteinsynthesization in ribosome causing the damage to the parasite, but it will not eliminate the parasitesrapidly from peripheral blood. The Clindamycin treatment on cats with babesiosis will not induct the sideeffects .
Keywords: Babesia sp. clindamycin, anemia, thrombocytopenia, parasitemia